Metafora Dalam Album Evergreen Motohiro Hata - Prasthaningrum, Arry Luh Ketut; Luhur Wedayanti, Ni Putu; Yuliani Giri, Ni Luh Kade (Humanis; Vol 17 No 3 (2016), 2017)
The title of this research is “Metaphor in Evergreen Album by Motohiro Hata”. This research aims to analyze the category, the meaning and the function of metaphor in Evergreen Album by Motohiro Hata. The theories that are used for analyzing arestylistics by Al-MA’ruf (2009) and metaphor by Knowless & Moon  (2006). The results of this research shows there are four metaphor identified in Evergreen CD 1: 1) personification; 2) simile; 3)metomyny; 4) synesthesia. In addition to it, the metaphor are functioned as follow : 1) to describe one’s feeling; 2) to show up impression whitin the lyrics; 3) to intensify the meaning.
Keywords: metaphor, song lyrics, meaning